2021
DOI: 10.1007/s00167-021-06584-x
|View full text |Cite
|
Sign up to set email alerts
|

Good healing potential of patellar chondral defects after all-arthroscopic autologous chondrocyte implantation with spheroids: a second-look arthroscopic assessment

Abstract: PurposeTo report second‐look arthroscopic assessment after all‐arthroscopic autologous chondrocyte implantation (ACI) for articular cartilage defects at the patella. MethodsA second‐look arthroscopy after all‐arthroscopic ACI using chondrospheres® (ACT3D) was performed in 30 patients with 30 full‐thickness retropatellar cartilage defects. The mean time from ACI to second‐look arthroscopy was 14.9 ± 16.3 (6–71) months. The quality of cartilage regeneration was evaluated by the International Cartilage‐Repair Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Interestingly, the present study showed that patients treated with ACI for flake fractures after patella dislocation show excellent results. The clinical outcome and return-to-sport rates were better than most of the results after patellofemoral ACI published so far [2,10,21,29,31]. In a current systematic review, Hinckel et al showed that patellofemoral cartilage restoration leads to good clinical results, but with a higher complication rate in comparison to the present study [10].…”
Section: Discussioncontrasting
confidence: 52%
“…Interestingly, the present study showed that patients treated with ACI for flake fractures after patella dislocation show excellent results. The clinical outcome and return-to-sport rates were better than most of the results after patellofemoral ACI published so far [2,10,21,29,31]. In a current systematic review, Hinckel et al showed that patellofemoral cartilage restoration leads to good clinical results, but with a higher complication rate in comparison to the present study [10].…”
Section: Discussioncontrasting
confidence: 52%
“…The literature search yielded 34 publications in PubMed and 70 in Web of Science. After removing 29 duplicates and screening the titles and abstracts, the full texts of 21 publications were screened, after which 18 [7,[10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27] were included and 3 [28][29][30] were excluded due to the use of xenogeneic materials [28] or antibiotics [29] in the cell culture, or the spheroids were formed by pelleting cells with centrifugation [30]. Two additional articles [16,31] were identified from citations (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…It has to be noted here that the adolescent patients were treated with chondrosphere in Germany under the German regulations. ACI with spheroids provided good patient-reported outcome scores [15][16][17][18][19], MRI [15,16,18,19], macroscopic [17,22], and histological [20] evaluations in patients with a routine treatment (Table 3).…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These chondrocyte spheroids were prepared by culturing 1 × 10 5 and/or 2 × 10 5 cells in agarose hydrogel-coated 96 well plates [ 182 ]. Patients Implanted with less than 70 spheroids showed substantial improvement in various clinical outcomes [ 180 , [183] , [184] , [185] ]. Based on these clinical results, it is expected that the treatment efficiency of limited cartilage can be improved if stem cell-based spheroids are used as cell therapy by replacing chondrocytes in this treatment technology with stem cells.…”
Section: Therapeutic Applications Of Stem Cell Spheroidsmentioning
confidence: 99%